2012
DOI: 10.5194/acpd-12-2395-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transport and outflow to the North Atlantic in the lower marine troposphere during ICARTT 2004

Abstract: An analysis of pollution plumes emitted from sources in the Northeastern US was based on observations from the International Consortium for Atmospheric Research on Transport and Transformation (ICARTT) 2004 field campaign. Particular attention was given to the relation of these plumes to coastal transport patterns in lower tropospheric layers throughout the Gulf of Maine (GOM) and their contribution to large-scale pollution outflow from the North American continent. Using measurements obtained during a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The prevailing stability of the stratification within offshore IBLs further provides for detachment from the surface once a continental air mass passes into the marine LT. This enables an efficient means for LT transport of trace gases and aerosols/dust over regional to intercontinental distances (Angevine et al, ; Dacre et al, ; Davis et al, ; Davis et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The prevailing stability of the stratification within offshore IBLs further provides for detachment from the surface once a continental air mass passes into the marine LT. This enables an efficient means for LT transport of trace gases and aerosols/dust over regional to intercontinental distances (Angevine et al, ; Dacre et al, ; Davis et al, ; Davis et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The air mass was broader and related to pollution outflow from a wider area of the East Coast, rather than the tight plume related to the strong emissions in the New York area (which would not be represented in the tracer simulations). Vertical profiles of a wide range of measurements are also shown in Davis et al (2012) from the same three flights, but the segments shown do not correspond to the Lagrangian intercepts identified by Methven et al (2006). Consequently the time evolution is not as apparent as shown in Fig.…”
Section: Tracers In the Modelmentioning
confidence: 89%
“…However, there were marked episodes of cross-coastal pollutant transport, some of which were observed by research aircraft as the air crossed the Atlantic to the Azores and Europe (Methven et al, 2006;Owen et al, 2006). Chemical processing following air masses for several days during these ICARTT Lagrangian cases has been examined in detail by Real et al (2008); Lee et al (2011);Cain et al (2012); Davis et al (2012).…”
Section: L Peake Et Al: Coastal Outflowmentioning
confidence: 99%
See 2 more Smart Citations